New developments and opportunities for AI in viticulture, pomology, and soft-fruit research: a mini-review and invitation to contribute articles - Fuentes, Sigfredo; Tongson, Eden; Gonzalez Viejo, Claudia (Frontiers in Horticulture, 2023)
Climate change constraints for horticultural production and emerging consumer requirements for sustainable and increased quality traits for fresh and processed horticultural products have pressured the industry to increase the efficiency, sustainability, productivity, and quality of horticultural products. Implementing Agriculture 4.0 using new and emerging digital technologies has increased the amount of data available from the soil–plant–atmosphere continuum to support decision-making in these Agrosystems. However, up to date, there has not been a unified effort to work with these novel digital technologies and gather data for precision farming. Artificial intelligence (AI), including machine/deep learning for data modelling, is considered the best approach to analyzing big data for the Horticulture and AgriFood sector in general. Hence, the term Agriculture/AgriFood 5.0 is starting to be used to identify the integration of digital technologies from precision agriculture and data handling and analysis using AI for automation. This mini-review focuses on the latest published work based on a soil-plant-atmosphere approach, especially those published works implementing AI technologies and modeling strategies.